Education and Decision-Making: An Experimental Study on the Framing Effect in China - Fan, Wen (Frontiers in Psychology, 2017)
China’s higher education expansion policy has been in effect for almost two decades. Under this policy, a growing number of youths have gained access to higher education, which aims to train students to be more rational. This study examines human rationality at a Chinese college through an experiment based on the risky-choice framing effect. The basic results show no classical framing effect with regard to individual decisions for the entire sample in a benchmark setting. However, when the participants’ roles were manipulated and subsamples were investigated, a significant framing effect was found that appeared to be role-related and that varied by sex. These results help to elucidate evaluations of the effects of China’s higher education policy and may assist in guiding further policy reforms.